2019
DOI: 10.5935/abc.20190141
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatic Fever: A Disease without Color

Abstract: BackgroundBrazil has approximately 30.000 cases of Acute Rheumatic Fever (ARF) annually. A third of cardiovascular surgeries performed in the country are due to the sequelae of rheumatic heart disease (RHD), which is an important public health problem.Objectivesto analyze the historical series of mortality rates and disease costs, projecting future trends to offer new data that may justify the need to implement a public health program for RF.Methods we performed a cross-sectional study with a time series analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 29 publications
(38 reference statements)
0
9
0
7
Order By: Relevance
“…Our search yielded a total of 2431 records of which 1692 were screened by title/abstract after duplicates were removed. One hundred seventy-nine records were sought for retrieval and ultimately 48 studies fulfilled the eligibility criteria [ 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 ]. A PRISMA [ 11 ] flow diagram of our search strategy and reasons for the exclusion of full-text articles can be seen in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our search yielded a total of 2431 records of which 1692 were screened by title/abstract after duplicates were removed. One hundred seventy-nine records were sought for retrieval and ultimately 48 studies fulfilled the eligibility criteria [ 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 ]. A PRISMA [ 11 ] flow diagram of our search strategy and reasons for the exclusion of full-text articles can be seen in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies reported RHD mortality regardless of their treatment; five were from Brazil [ 30 33 37 49 63 ], while the other two were from Peru [ 54 ] and Venezuela [ 34 ]. Studies reported data with different measures (e.g., proportions, rates) with four of them reporting mortality rates.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, 22% of the study population had rheumatic disease, the most prevalent etiology of valve disease in Brazil. 2 The authors found no difference in mortality rates after 10 years of follow-up; however, the implantation of a mechanical prosthesis was associated with a lower rate of reoperation (with no reoperation in the mechanical prosthesis group). When analyzing specifically the bioprosthesis reoperations, patients under 30 years old had the highest rates, compared to those older than 50 years, and even to patients between 30 and 49 years of age.…”
mentioning
confidence: 87%
“…Um declínio na doença valvar reumática foi observado nas últimas décadas, [14][15][16][17] com a etiologia degenerativa como a causa mais comum em países desenvolvidos. No entanto, a carga da doença valvar reumática persiste em países de rendas baixa e média, com prevalência (a doença afeta até 7 em 1000 crianças escolares no Brasil, versus 0,1-0,4 em 18 e mortalidade (275 mil mortes por ano no mundo) significativas. 17 Um estudo recente de Glaser et al 19 indicou que as bioprósteses têm maior risco de infecção em comparação a válvulas mecânicas, mas mais estudos ainda são necessários.…”
Section: Fatores De Riscounclassified